The effect of clustering of Si nanowires produced by the metal-assisted chemical etching method on their anti-reflecting properties - Skrypnyk, I.I.; Nichkalo, S.I.; Shtangret, N.O. (Physics and Chemistry of Solid State, 2024)
Silicon nanowires are valuable for their compatibility with silicon technology and unique properties. Using metal-assisted chemical etching, we produced silicon nanowires and studied the effects of clustering, roughness, and length on wetting. Hydrophobicity depends on silicon nanowires clustering, which is influenced by length. The highest contact angle ( 95º) was for 8.5-μm long nanowires. Below 8 μm, minimal clustering promotes wetting, while longer nanowires form larger clusters and hydrophobic surfaces. The Cassie–Baxter model applies initially, transitioning to the Wenzel model over time. Adjusting surface morphology can improve anti-reflective properties. Metal-assisted chemical etching offers control over the silicon nanowires’ length and wettability, benefiting silicon-based device development.